Обзор фауны кокцид (Insecta, Homoptera, Coccoidea) Крыма по ландшафтным районам - Терезникова, Е.М. (Вестник зоологии, 1968)
The nature of various landscape areas of the Crimea is not the same. This fact explaines a great difference in faunistic composition, ecology and geographical distribu-tion of their inhabitants. The fauna of the mountain Crimea is especially rich in coccids. 90 species out of 121 are met here, a part of them being only within the limits of this area. For example Gueriniella serratulae Fonsc., Pseudococcus azarititnus Ehrh., Ps. citri Rissoare met only on the south coast of the Crimea; Margarodes mediterraneus Silv., Kuwania minuta Kuw., Luzulaspis taurica BorcIis. are observed only on the south slopes of the Crimea mmintains; Psettdococcus jai/aensis Kir. is an endemic of the mountain pasture. 24 species are known in the steppe Crimea, and only 7 species are registrated for the present on the Kerch Peninsula. It is mainly the typical species with a wide areal distributed in steppe districts not only of the Ukraine but often far beyond its boundaries.